Analysis of 18 urinary mercapturic acids by two high-throughput multiplex-LC-MS/MS methods - Pluym, Nikola; Gilch, Gerhard; Scherer, Gerhard; Scherer, Max (Analytical and bioanalytical chemistry, 2015)
Mercapturic acids (MAs) are metabolic end products formed from conjugates between glutathione and electrophilic compounds. MAs are, therefore, suitable biomarkers of exposure to toxicants, which are either electrophiles by themselves or metabolized to electrophilic intermediates. We developed and validated two LC-MS/MS methods which allow the complementary, rapid, and sensitive determination of MAs derived from acrolein, acrylamide, acrylonitrile, benzene, 1,3-butadiene, crotonaldehyde, N,N-dimethylformamide, ethylene, ethylene oxide, vinyl chloride, propylene oxide, styrene, toluene as well as methylating and ethylating agents. Since separate determinations of single or small groups of MAs are time-consuming and expensive, we multiplexed several individual methods into two LC-MS/MS methods covering 18 individual mercapturic acids. Method validation according to FDA guidelines showed excellent results in terms of robustness, accuracy, and sensitivity of the methods. Moreover, the use of a minimal, simple, and straightforward sample cleanup procedure further accelerated the analytical workflow, which allows a time- and cost-efficient analysis of up to 18 MAs derived from various toxicants in environmental levels. The methods were applied to urine samples derived from a strictly diet-controlled clinical study, including 25 smoking and 25 non-smoking subjects. Significant increase in the urine concentrations in smokers as compared to non-smokers (p < 0.01; Student t test) was observed for 13 individual MAs. Moreover, a dose dependence was obtained for the majority of the analytes. In conclusion, the newly developed assays represent a powerful tool for the fast and reliable quantification of 18 MAs in clinical studies. A first method application suggests several suitable biomarkers for nine relevant toxicants in tobacco smoke.